KEMAMPUAN KOMUNIKASI SAINS DAN HASIL BELAJAR SISWA PADA MATERI SISTEM PERNAPASAN MENGGUNAKAN FASILITAS MOBILE-LEARNING - Burhani, Sismi Harti (2017)
This study will discuss about SSC (Science Communication Competence) and student learning outcomes through mobile-learning. Nowadays learning is faced with various kinds of challenges and problems. The problems is the development of technology, the use of learning media and learning resources. In addition to technological developments, there are several demands from the 2013 curriculum for students to communicate well. Results of previous SSC research by Soniyana (2016) categorize the ability of science communication owned by students into the category enough, less even less once. The results of Soniayana (2016) are same with research Herdianti (2013) and Amelia (2015). Previous research has been linked to plant and ecosystem material. And not yet SSC studies have examined the respiratory system material. From both of these problems, the researcher assessed that there is still much to be studied and examined related to the SSC and students' learning outcomes with learning resources and alternative learning media that is mobile-learning. The purpose of this study was to identify the communication skills of science and student learning outcomes in the respiratory system through mobile-learning. Science communication includes three categories (Cognitive Categories, Content Knowledge and Volitional Change) categories based on research developed by Kulgunmeyer and Schecker (2013) and learning outcomes include mastery of concepts, students' social attitudes and student performance. This study included quasi experiments with nonequivalent control group design. Instrument that used observation rubric, student questionnaire, concept mastering test, affective judgment (attitude) and attitude assessment. This research was conducted in one of the SMA Negri in Bandung by using two class samples Convenience sampling. The conclusion obtained from this research is to have a positive contribution to the ability of science communication and student learning outcomes. Penelitian ini akan membahas kemampuan komunikasi sains dan hasil belajar siswa melauli pembelajaran dengan mobile-learning. Hal ini dilatarbelakangi karena saat ini pembelajaran dihadapkan dengan berbagai macam tantangan dan permasalahan. Diantara permasalahannya adalah perkembangan teknologi, pemakaian media pembelajaran dan sumber belajar. Selain perkembangan teknologi, ada beberapa tuntutan dari kurikulum 2013 untuk siswa dapat berkomunikasi dengan baik. Hasil penelitian komunikasi sains sebelumnya yang dilakukan oleh Soniyana (2016) mengategorikan kemampuan komunikasi sains yang dimiliki siswa ke dalam kategori cukup, kurang bahkan kurang sekali. Hasil Soniayana (2016) selaras dengan penelitian Herdianti (2013) dan Amelia (2015). Penelitian sebelumnya terkait dengan materi tumbuhan dan eksosisis dan belum ada penelitian komunikasi sains yang mengkaji materi sistem pernapasan. Dari kedua masalah tersebut peneliti menilai masih harus banyak yang dikaji dan diteliti terkait kemampuan komunikasi sains dan hasil belajar siswa dengan sumber belajar dan media pembelajaran alternative yaitu mobile-learning. Tujuan dari penelitian ini adalah untuk mengidentifikasi kemampuan komunikasi sains dan hasil belajar siswa pada sistem pernapasan melalui pembelajaran mobile-learning. Komunikasi sains mencakup tiga kategori (Cognitive Categories, Content Knowledge dan Volitional change) kategori tersebut berdasarkan penelitian yang dikembangkan oleh Kulgunmeyer dan Schecker (2013) dan hasil belajar mencakup penguasaan konsep, sikap sosial siswa dan kinerja siswa. Penelitian ini termasuk kuasi eksperimen dengan nonequivalent control group design dengan perangkat instrumen rubrik observasi, angket siswa, tes penguasaan konsep, penilaian afektif (sikap) dan penilaian sikap .Penelitian ini dilakukan disalah satu SMA Negri di Kota Bandung dengan menggunakan sample dua kelas yang dimbil dengan convenience sampling. Kesimpulan yang didapat dari penelitian ini adalah memiliki kontribusi positif terhadap kemampuan komunikasi sains dan hasil belajar siswa. Kata Kunci : Kemampuan Komunikasi Sains, Hasil Belajar, Mobile-Learning